Lines, Landscapes & Lore : Waterval Boven as a case study for regenerative heritage remodelling as a strategy for small towns rejuvenation - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2019)
Dissertation (MArch (Prof))--University of Pretoria, 2018.